Parent’s Role in Online Distance Learning During the Covid-19 in Sorong City, West Papua - Djafar, Hilman; Rasid, Ruslan; Haris Panai , Abdul; Kadir Husain , Abdul (International Journal of Educational Research & Social Sciences, 2021)
The imbalance in the social structure in Emile Durkheim's opinion is at least influenced by three factors, namely equlibrium, external and consensus. The Covid-19 pandemic that befell mankind from various directions has caused a rigid shift in student learning. Where initially, educators had a big role in student learning completeness during the education level. However, after this outbreak there was a shift in function. Teachers do not fully play an active role in student learning completeness. However, sometimes the parents at home take the role. Therefore. The purpose of this study was to analyze parent’s role in online distance learning. The results of this study state that: 1). The teacher only functions as a giver and receiver of tasks; 2) Parents apart from being caregivers of students at home, they also have a dual task